1990
DOI: 10.1021/ie00103a034
|View full text |Cite
|
Sign up to set email alerts
|

Single-drop mass transfer in the water-toluene-acetone system

Abstract: An experimental study of fundamental mass-transfer characteristics was carried out in which acetone was transferred between water and toluene. All possible arrangements were involved; i.e., acetone was transferred in both directions, and both water and toluene were used as dispersed phases. With technical-grade solvents, the transfer rates were 2-10 times higher than calculated for rigid spheres, and on increasing the system purity, this increase grew to between 30 and 70 times. A previously derived empirical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
2
34
0
Order By: Relevance
“…In this configuration, mass transfer is higher if acetone is transferred from the dispersed phase into the continuous phase. Temos et al (1996) confirmed the enhancement of mass transfer when the solute transfer direction is d → c. In order to describe the increased mass transfer due to interfacial instabilities, Steiner et al (1990) introduce an effective diffusivity, Henschke and Pfennig (1999) describe the enhanced mass transfer with an "instability constant" which has to be identified in single-drop experiments. Schulze et al (2003) confirmed the chaotic flow structure inside drops due to Marangoni convection in decolourization experiments.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In this configuration, mass transfer is higher if acetone is transferred from the dispersed phase into the continuous phase. Temos et al (1996) confirmed the enhancement of mass transfer when the solute transfer direction is d → c. In order to describe the increased mass transfer due to interfacial instabilities, Steiner et al (1990) introduce an effective diffusivity, Henschke and Pfennig (1999) describe the enhanced mass transfer with an "instability constant" which has to be identified in single-drop experiments. Schulze et al (2003) confirmed the chaotic flow structure inside drops due to Marangoni convection in decolourization experiments.…”
Section: Introductionmentioning
confidence: 77%
“…Concerning moving drops, Steiner et al (1990) reported that mass transfer enhancement in the toluene/acetone/water system is strongly dependent on the mass transfer direction. Higher rates were obtained if toluene is the dispersed phase.…”
Section: Introductionmentioning
confidence: 99%
“…Alves et al (2005) applied the stagnant-cap model on experimentally obtained terminal velocity values of air bubbles rising in water in order to take the effect of bubble contamination on rise velocity and mass transfer into account. Large droplets that are important in engineering applications were studied experimentally by various authors (Hendrix et al, 1967;Mekasut et al, 1979;Steiner et al, 1990). Based on the experimental results these papers also treat modelling issues.…”
Section: Article In Pressmentioning
confidence: 99%
“…Thus, the modified model can be applied in circulation conditions or even oscillation conditions. Steiner (1986 and1990) tested this method with numerous data and further correlated the empirical factor against the physical properties. Both Saien et al (2012) and Sun et al (2014) used this correlation to predict the mass transfer process in their works.…”
Section: Modeling the Overall Mass-transfer Coefficientmentioning
confidence: 99%